Digenic Inheritance and Gene-Environment Interaction in a Patient With Hypertriglyceridemia and Acute Pancreatitis - Yang, Qi; Pu, Na; Li, Xiao-Yao; Shi, Xiao-Lei; Chen, Wei-Wei; Zhang, Guo-Fu; Hu, Yue-Peng; Zhou, Jing; Chen, Fa-Xi; Li, Bai-Qiang; Tong, Zhi-Hui; Férec, Claude; et al. (Frontiers in Genetics, 2021)
The etiology of hypertriglyceridemia (HTG) and acute pancreatitis (AP) is complex. Herein, we dissected the underlying etiology in a patient with HTG and AP. The patient had a 20-year history of heavy alcohol consumption and an 8-year history of mild HTG. He was hospitalized for alcohol-triggered AP, with a plasma triglyceride (TG) level up to 21.4 mmol/L. A temporary rise in post-heparin LPL concentration (1.5-2.5 times of controls) was noted during the early days of AP whilst LPL activity was consistently low (50 70% of controls). His TG level rapidly decreased to normal in response to treatment, and remained normal to borderline high during a 3-year follow-up period during which he had abstained completely from alcohol. Sequencing of the five primary HTG genes (i.e., LPL, APOC2, APOA5, GPIHBP1 and LMF1) identified two heterozygous variants. One was the common APOA5 c.553G>T (p.Gly185Cys) variant, which has been previously associated with altered TG levels as well as HTG-induced acute pancreatitis (HTG-AP). The other was a rare variant in the LPL gene, c.756T>G (p.Ile252Met), which was predicted to be likely pathogenic and found experimentally to cause a 40% loss of LPL activity without affecting either protein synthesis or secretion. We provide evidence that both a gene-gene interaction (between the common APOA5 variant and the rare LPL variant) and a gene-environment interaction (between alcohol and digenic inheritance) might have contributed to the development of mild HTG and alcohol-triggered AP in the patient, thereby improving our understanding of the complex etiology of HTG and HTG-AP.